Deflection measuring system for floating dry docks. (1st May 2016) - Korotaev, Valery V.; Pantiushin, Anton V.; Serikova, Mariya G.; Anisimov, Andrei G.
Abstract: Reliable measurement of a deflection magnitude refers to one of the most important tasks in floating dry dock operation. Current and accurate information about the deflection can prevent structural damage and failure by activating alarms and on-board deflection compensation systems. This paper describes the development of a deflection measuring system for floating dry docks. The measuring system is capable of measuring the actual deflection of a dock structure in real-time and fully automatic mode. The system consists of a set of reference marks based on light emitting diodes and a measurement unit with two oppositely directed camera-based channels. The measurement unit is placed in the middle of a wing deck of the dock. The measurement unit and the reference marks are aligned along the wing deck. The accuracy of deflection measurement of ± 1.5 mm in the range of ±150 mm for the docks in length more than 100 m was achieved during laboratory tests. The system resistance to harsh environment (salt fog, temperature gradient, high humidity, etc.) and the ability to perform measurements in 24/7 regime was proved through field tests at a floating dry dock in operation. Abstract : Graphical abstract: Abstract : Highlights: Camera-based measuring system for a floating dry dock deflection is developed and tested. Deflection model of hull structure is considered. Deflection calculation algorithm is developed. Error of deflection measuring is less than ±1.5 mm at a distance of 100 m.